Considering mystagogy as method in Biblical Spirituality - Lombaard, Christoffel (HTS teologiese studies, 2020)
In this contribution, the mystagogic engagement with Bible texts is considered. Good and bad reasons for drawing on the Bible are considered, both within personal and cultural frameworks. Different exegetical procedures are taken into review to inform a discussion of particularly the mystagogic engagement with the text. The latter is characterised by seeking faithfrom the biblical texts. For theological reasons, historical exegesis is proposed as particularly suited to mystagogic facilitation.Contribution: There are good and bad reasons for drawing on the Bible, within personal and cultural frameworks. Different exegetical procedures inform a discussion of mystagogic engagement with the text, seeking faith from the biblical texts. Historical exegesis is proposed as particularly suited to mystagogic facilitation.